A survey on knowledge-based systems for ship design and ship operation. (1st January 2013) - Bertram, Volker
The paper gives a survey of knowledge-based systems (KBS) for ship design and ship operation over the past three decades. While there are several commercial applications of KBS in ship operation, applications in ship design have remained almost exclusively in the academic stage.